A user acceptance of robot technology for elderly / Rafiza Azhar - Azhar, Rafiza (2015)
Robot is not a new technology in an industry like manufacturing and health care which they were designed, but a combination of artificial intelligence that can produce a new robot technology that can help people in many ways and also as facilitating technologies. This research used the Technology Acceptance Model (TAM) as a model to evaluate the level of acceptance for elderly user. Five elderly participants interact to be as respondents for this research and the interaction was followed by a qualitative research and structure interview to elicit their opinions and feedback. There are two objectives of the research, (1) to study user acceptance of robot in their everyday life, and (2) to identify the existing model of user acceptance. This research used the qualitative research and five respondents will be chosen to be as participant.